15=-a+(-a)+(-a)
a=-5
Question
Updated 270 days ago|6/8/2023 4:42:42 AM
f
Rating
3
15 = -a + (-a) + (-a)

15 = -a - a - a;

15 = -3a;

a = -15/3;

a = -5.
Added 270 days ago|6/8/2023 4:42:42 AM

Questions asked by the same visitor
15=-a+(-a)+(-a)
Weegy: You need a set value of a before you can solve the problem (More)
Question
Updated 10/19/2014 6:34:52 PM
15 = -a-a-a
15 = -3a
--> a = 15/-3 = -5
15 = -a + (-a) + (-a)

15 = -a - a - a;

15 = -3a;

a = -15/3;

a = -5
38,929,473
Popular Conversations
S
L
Points 155 [Total 735] Ratings 0 Comments 155 Invitations 0 Offline
S
L
Points 93 [Total 1554] Ratings 0 Comments 93 Invitations 0 Offline
S
L
Points 59 [Total 2252] Ratings 0 Comments 59 Invitations 0 Offline
S
L
P
R
L
P
L
P
P
P
R
Points 35 [Total 17914] Ratings 0 Comments 35 Invitations 0 Offline
S
L
P
1
P
Points 11 [Total 2766] Ratings 0 Comments 11 Invitations 0 Offline
S
L
Points 10 [Total 356] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 24] Ratings 1 Comments 0 Invitations 0 Online
S
L
P
Points 7 [Total 3023] Ratings 0 Comments 7 Invitations 0 Offline
S
Points 4 [Total 4] Ratings 0 Comments 4 Invitations 0 Offline
S
Points 4 [Total 63] Ratings 0 Comments 4 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.